PENGOLAHAN NUGGET BERBAHAN DASAR IKAN CAKALANG PADA UMKM TERATAI DESA KATIALADA, KABUPATEN GORONTALO UTARA, PROVINSI GORORNTALO - Astuti, Ida; Ngabito, Meriyanti; Adipu, Yulianty; Yuningsih Noor, Sri; Darmawan, Darmawan; Damima, Stievhany; Pangalila, Raian; Pakaya, Delin (Insan Cita : Jurnal Pengabdian Kepada Masyarakat, 2026)
Teratai Micro, Small, and Medium Enterprises (MSMEs) in Katialada Village is a business actor that utilises local potential in the form of skipjack tuna (Katsuwonus pelamis) by innovating its processed products into nuggets. This community service activity aimed to provide training on the skipjack tuna nugget processing technique and to identify the development of skipjack tuna nuggets within this MSMEs. The methods employed were the approach method, demonstration and training, and evaluation. The results indicated that the nugget production process includes the stages of raw material preparation (filleting, washing), mixing the batter (comminuted fish meat, flour, spices, and binders), moulding, steaming, coating with breadcrumbs, freezing, and packaging. The resulting nugget product has a distinctive savoury skipjack tuna flavour, a soft interior texture yet crispy exterior, and high nutritional value, particularly in protein. However, the challenges faced by MSMEs include limited capital for expansion, the need for a cold chain to maintain the shelf life of frozen products, and competition with commercial chicken nuggets. It is concluded that Teratai MSME's skipjack tuna nuggets have good market prospects as a value-added alternative product. For further development, effective marketing strategies, flavour diversification, and support in terms of capital and preservation technology are needed to enhance competitiveness and business scalability. Keywords: skipjak tuna, fish nuggets, MSMEs, diversifikation, produk, value-Added